Association of baseline osteocalcin and femoral neck bone mineral density in healthy women with future risk of fractures, cardiovascular disease, diabetes and death - Pan, Zheng-Can; Yang, Yu-Ying; Chen, Xiao-Jing; Jiang, Tao; Song, Jia-Xi; Sheng, Chun-Xiang; Wang, Yi-Zhu; Xu, Min; Deng, Yan-Hua; Yu, Guang-Ping; Sun, Li-Hao; Zhao, Hong-Yan; et al. (Frontiers in Endocrinology, 2025)
PurposeThis study aimed to explore relationships between baseline bone metabolism markers and long-term outcomes, collectively referred to as fractures, cardiovascular diseases, diabetes and all-cause death (FCDD), in healthy women at baseline and identify predictive markers for outcome.MethodsThis study included 356 healthy women and assessed baseline bone turnover markers—osteocalcin, C-telopeptide of type I collagen—as well as bone mineral densities (BMDs) at lumbar spine (L1-4), femoral neck (FN) and total hip (TH). A 16-year retrospective follow-up via telephone questionnaire tracked FCDD occurrence. Statistical tests, including univariate analysis, forward stepwise regression and logistic regression analysis, were used to determine correlations between baseline markers and FCDD.ResultsAmong 356 participants, 291 (81.7%) completed follow-up; among these 291 subjects, 109 (37.5%) experienced FCDD. 47 participants experienced fractures (16.2%), 27 developed diabetes (9.3%), 25 experienced cardiovascular events or mortality (8.6%). Stepwise regression identified osteocalcin (odds ratio: 0.938, 95% confidence interval: 0.895–0.980, P = 0.006) and FN BMD (odds ratio: 0.066, 95% confidence interval: 0.008–0.490, P = 0.009) as independent predictors. However, logistic regression revealed that the protective effect of FN BMD was attenuated after adjusting for age, body mass index, years since menopause, whereas osteocalcin remained significant (P < 0.05). Heatmap visualization revealed the lowest FCDD risk among both markers in the highest tertiles (P = 0.002).ConclusionOur study shows that baseline osteocalcin is independently associated with long-term FCDD outcomes in healthy women. These insights offer valuable guidance for the development of personalized health prevention and intervention strategies.